The Effects of Perceived Stigma on the Concealment of Disease and Satisfaction with Life in Patients with Epilepsy: An Example in Eastern Turkey - Turan, Gulcan Bahcecioglu; Ozer, Zulfunaz; Ozden, Beyan (Wiley, 2022)
Background. Stigma and exclusion are common features of epilepsy in both developed and developing countries, and they cause a significant burden associated with the condition. At the same time, although it varies from country to country depending on cultural differences and economic conditions, having epilepsy causes significant social consequences. Objective. This study was conducted to examine the effects of perceived stigma on the concealment of disease and satisfaction with life in patients with epilepsy living in the east of Turkey. Methods. This cross-sectional and descriptive study was carried out with 150 patients who met the study criteria and who agreed to participate in the study between March and July 2021 in a university hospital in Elazig, east of Turkey. The data were collected using a personal information form, an Epilepsy Stigma Scale (ESS), a Concealment of Epilepsy Scale (CES), and a Satisfaction with Life Scale (SWLS). Results. The total mean ESS score of the patients was 40.7 & PLUSMN; 9.04, the total CES mean score was 57.19 & PLUSMN; 12.57, and the total SWLS mean score was 6.68 & PLUSMN; 2.86. When the regression coefficients were examined, it was found that the ESS variable had a positive and significant effect on the CES, while the ESS and the CES had a negative and significant effect on satisfaction with life (p < 0.001). Conclusion. It was found that the patients had high levels of perceived stigma and concealment of epilepsy and low satisfaction with life levels. It was also found that the patients concealed their disease for fear of stigma, which negatively affected their satisfaction with life.
Keywords: Quality-of-Life; Health; Impact; Community; People